CIM-powered physics-based assessment of wind damages to building clusters considering trees - Donglian Gu; Qianwen Shuai; Yixing Wang (Developments in the Built Environment, 2023)
It is important to obtain accurate predictions of wind damage to building clusters for reducing wind-induced economic losses. To this end, a city information model-powered physics-based method for assessing the wind damage to building clusters considering trees was proposed. The influence of trees on wind damage was investigated based on two virtual standard building clusters, revealing that trees can play a shielding role to reduce the risk level of buildings. The reliability and feasibility of the method were demonstrated based on a case study of a manufacturing factory. Moreover, the applicability of the method in city-scale applications was illustrated based on a large urban area covering 619 buildings and 19,740 trees. Based on meteorological forecasting data, the proposed method can help city managers identify and reinforce the building with a high damage risk before strong wind events, thus promoting a safer city.